CT SCAN 128 SLICES TECHNOLOGY IN EMERGENCY PNEUMOTORAX AND PNEUMOMEDIASTINUM CASES - Lilik Lestari; Muhammad Harris Sis Sultansyah (Center for Biomechanics, Biomaterials, Biomechantronics and Biosignal Processing (CBOIM3S), 2022)
Pneumothorax and pneumomediastinum are complications of mechanical ventilation of the pleural and mediastina cavities. This study aims to report the findings of a 128-slice 3D chest scan with an axial coronal view for a case of pneumothorax and pneumomediastinum. Research conducted at dr. Ario Wirawan, Salatiga. The study used a CT scan 128-slice type Ingenuity CT 120 kV, series 502 idose 4, slice thickness 0.64 mm, zoom 1.0 and used contrast. The CT scan imaging results were qualitatively analyzed by experts. The results showed four cases with pneumothorax and pneumomediastinum, and only pneumothorax was found in seven cases.